Analyzing the impact of economic growth and FDI on sustainable development goals in China: insights from ecological footprints and load capacity factors - Güler, İlkay; Naimoğlu, Mustafa; Şimşek, Orhan; Adalı, Zafer; Özbek, Sefa (Frontiers in Environmental Science, 2025)
This study investigates the impact of economic growth and foreign direct investment (FDI) on China’s sustainable development goals (SDGs), specifically Zero Hunger (SDG 2), Life Below Water (SDG 14), and Life on Land (SDG 15). It examines ecological footprints and load capacity factors (LCFs) in cropland, fishing, forest, and grazing land using Fourier bootstrap autoregressive distributed lag (ARDL) cointegration analysis and fully modified ordinary least squares (FMOLS) estimators. The study covers the period from 1979 to 2022. Key findings reveal that while GDP and FDI often exacerbate environmental degradation, urbanization and value-added agriculture, forestry, and fishing (FAFGDP) improve sustainability in some areas. The study confirms the pollution haven hypothesis for most models, suggesting that China’s legal and regulatory frameworks may inadequately mitigate FDI’s adverse environmental effects. The Environmental Kuznets Curve (EKC) hypothesis is not supported as GDP growth generally increases ecological footprints. However, trade openness and urbanization show positive influences on environmental sustainability. Policy recommendations include enhancing energy efficiency, promoting renewable energy, implementing green technologies in agriculture and urban development, and revising FDI policies to incentivize environmentally friendly practices. These strategies are crucial for achieving China’s sustainable development goals and mitigating the pressures of human activities on natural resources.